Application of Trichoderma to Prevent Phaeomoniella chlamydospora Infections in Organic Nurseries - Di Marco, S.; Osti, F. (Phytopathologia Mediterranea, 2007)
In order to prevent or reduce infection in grapevine nurseries, greenhouse and nursery trials were carriedout to evaluate the effects of Trichoderma harzianum (Rootshield®) on the morpho-physiological characteristicsof grapevine and on Phaeomoniella chlamydospora artificially inoculated on potted cuttings. The long-distance activityof Trichoderma against Botrytis cinerea was also examined. The study was performed in a commercial nurserywhere plants were grown organically. Results greatly depended on the vine-growth stage at which Trichoderma wasapplied. Treatment at rooting was the most effective, whilst callusing-box application or treatments at both rootingand callusing gave inconsistent but generally negative results. Treatment at rooting further improved the quantitativeand qualitative characteristics of the root system, and increased the percentage of certifiable vines produced.Moreover, Trichoderma application also reduced the necrotic area caused by B. cinerea inoculated on the leavescollected from Trichoderma-treated plants and the extent of necrosis of P. chlamydospora-inoculated cuttings. Thisreduction in necrosis was significantly higher 15 months after inoculation. On the other hand, Trichoderma increasedvine mortality at the end of the growing season compared with untreated plants. On the whole, only when itwas applied at rooting did Trichoderma produce positive effects on the morpho-phisiological characteristics of grapevineand increased its tolerance to stress–related diseases, such as forms of esca found in the nursery.